2016
DOI: 10.1177/1043454216631952
|View full text |Cite
|
Sign up to set email alerts
|

BK Virus-Associated Hemorrhagic Cystitis After Allogeneic Hematopoietic Stem Cell Transplantation in the Pediatric Population

Abstract: We conclude that HC-BKV is a frequent complication after allo-HSCT. CDV therapy can be effective but controlled clinical trials are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…They declared acute GVHD as a risk factor for BKV infection. The rate of HC was 6.5% in allogeneic HSCT patients and it is close to 9% rate of Kwon et al (15) and 8.9% rate of Lee et al (17), and similar with 6% rate of Mori et al (18), but lower than the other studies (7,10,11,19,20). According to our results, HC occurred median 56 days after HSCT and it is close to result of Lee et al (18, 69 days).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…They declared acute GVHD as a risk factor for BKV infection. The rate of HC was 6.5% in allogeneic HSCT patients and it is close to 9% rate of Kwon et al (15) and 8.9% rate of Lee et al (17), and similar with 6% rate of Mori et al (18), but lower than the other studies (7,10,11,19,20). According to our results, HC occurred median 56 days after HSCT and it is close to result of Lee et al (18, 69 days).…”
Section: Discussionsupporting
confidence: 88%
“…According to our results, HC occurred median 56 days after HSCT and it is close to result of Lee et al (18, 69 days). But the many other studies reported that HC developed in a shorter time (12,14,15,(19)(20)(21).…”
Section: Discussionmentioning
confidence: 94%
“…Atilla et al 28 investigated the relationship between BKV viremia and HC in allogeneic HSCT recipients; they claimed that the presence of BKV viremia significantly increased the risk of developing HC, and more severe HC developed in patients with a higher viral load. HC is seen in 2‐66% of patients undergoing HSCT, depending on the underlying disease, HSCT type, and the age of the patient 10‐12,29 . The frequency of HC development was reported as 20.7% by Perez Huertez et al, 29 9% by Kwon et al, 27 and 18.8% by Cesare et al 11 Hayden et al 30 claimed that the negative predictive value is higher than the positive predictive value when BKV DNA is not detected even if a high viral load is associated with cystitis.…”
Section: Discussionmentioning
confidence: 99%
“…The response rate observed across retrospective case series varies from 60% to 86%. 40,44,45 Renal dysfunction is the main adverse effect observed with intravenous cidofovir, with reported incidences of up to 50%. 44 Grades 3 and 4 BKV-related HC warrant treatment with cidofovir till clinical response or a maximum of 4 weeks.…”
Section: Treatmentmentioning
confidence: 99%